Line spread test: moving toward clinical implications - Lund, Annelise; Garcia, Jane Mertz; Chambers, Edgar, IV (My University, 2013)
Purpose: Preparing modified liquids to a target level of consistency as specified by the speech-language pathologist is critical to service delivery. This study explored the value of line spread testing (distance a liquid flows) in comparison to viscometry readings for differentiating a variety of modified liquids prepared to nectar-thick vs. honey-like consistency. Method: We tested combinations of four thickening products (three starch-based and one gum-based thickener) prepared with six serving temperature beverages that had various levels of fat, fiber, and added nutrients. A total of 32 product/liquid combinations measured within the target range of 80-800 centipoise (cP). Measurements were recorded from the Line Spread Test (after 60 seconds of spread) and a Brookfield RVDV-II+ viscometer. Results: Nectar-thick and honey-like consistencies significantly differed in their degree of spread. Using our line spread apparatus, a value of 4.5 centimeters (cm) differentiated between nectar-thick and honey-like consistencies. There was an inverse correlation (-.75) between viscometer data and line spread test results across consistencies. Conclusions: The Line Spread Test may be a cost effective method for assisting with staff training in the preparation of thickened liquids in different care environments by providing visual feedback about sample consistency.
Line spread as a visual clinical tool for thickened liquids
Keywords: Dysphagia; Swallowing; Thickened liquids